The role of monetary policy in the aggregate indicator of banking stability in Iraq: An applied research in the Central Bank of Iraq for the period (2010 - 2017) (Journal of Accounting and Financial Studies ( JAFS ), 2019)
The research sought to demonstrate the effectiveness of monetary policy in banking stability by measuring the impact of monetary policy in the composite index of banking stability in Iraq for the period 2010/2017, as the stability of the financial system is one of the main objectives that the Central Bank is keen to achieve along with other objectives to ensure the performance Effective for all economic units, this is what prompted the central banks to give more attention in ensuring the safety, durability and stability of their financial systems, and the increasing interest by the Central Bank of Iraq in the subject of financial stability stems from its responsibility in ensuring a sound and stable financial system. Maintain it and minimize potential risks after forecasting, and this is what encouraged him to make the financial stability first goal within the stated strategy for the period (2016/2020).  The researcher reached a number of conclusions, the most prominent of which is that the most important quantitative tools that are related to the aggregate index of banking stability are: cash window, legal reserve and transfer window respectively. The most important recommendations were to take into account the stability of the banking when drawing monetary policies to know the size and trends of the shock on the side of domestic credit, and the probability of default and low capital adequacy ratio, and therefore hedge and caution against any problems that occur in the banking sector.